Tinjauan Konteks Situasi Desain Mural Sebagai Bahasa Visual “Dampak Polusi Kendaraan Pada Kesehatan masyarat” Analisis Halliday - Haryono Haryono; Qatrunnada Qatrunnada; Irfan Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
Murals are positioned as texts that communicate social messages through a combination of visual and symbolic, and act as a medium for environmental advocacy in public spaces. This study discusses the mural design with the theme